2010
DOI: 10.1143/apex.3.031001
|View full text |Cite
|
Sign up to set email alerts
|

An AlN Sacrificial Buffer Layer Inserted into the GaN/Patterned Sapphire Substrate for a Chemical Lift-Off Process

Abstract: InGaN-based light-emitting diodes (LEDs) grown on triangle-shaped patterned sapphire substrates were separated through a chemical lift-off process by laterally etching an AlN sacrificial layer at the GaN/sapphire substrate interface. After the epitaxial growth, an air-void structure was observed at the patterned region on the sapphire substrate that provided an empty space to increase the lateral etching rate of the AlN buffer layer. The lateral etching rate of the AlN buffer layer was calculated at 10 mu m/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…On the one hand it has been argued that the formation of voids plays a key role in stress relaxation, crack suppression and TDs reduction [22,23], while on the other hand voids can help in effectively diffracting light into the escape-cone and thus increasing the escape probability in light emitting structures [24]. Furthermore, the presence of voids can also assist in the lift-off process for the removal of substrates [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand it has been argued that the formation of voids plays a key role in stress relaxation, crack suppression and TDs reduction [22,23], while on the other hand voids can help in effectively diffracting light into the escape-cone and thus increasing the escape probability in light emitting structures [24]. Furthermore, the presence of voids can also assist in the lift-off process for the removal of substrates [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The laser scribing depth was 2.2 μ m to reach the as-grown 12-period n + -GaN/u-GaN stack structure by using a 355 nm laser. After the lateral wet etching process, the Si-heavy doped n + -GaN:Si layer was transformed into a nanoporous GaN layer through the doping-selective electrochemically etching process in a 0.5 M nitride acid solution at positive 8 V external bias voltage 24 . After the EC-etching process, a high refractive index n-type GaN:Si layer was transformed into a low refractive index nanoporous GaN layer.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have proposed several useful growth techniques to improve the crystal quality, such as epitaxial lateral overgrowth (ELOG) [4][5][6], pendeo-epitaxy (PE) [7], maskless PE [8], cantilever epitaxy [9], facet-controlled epitaxial lateral overgrowth (FACELO) [10,11], SiN x /GaN buffer layer [12], abbreviated growth mode [13][14][15], and freestanding GaN substrates [16][17][18]. Patterned sapphire substrate [19] and embedded air voids method [20,21] have been developed to further enhance the light extraction efficiency (LEE) of light-emitting diodes (LEDs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, embedded air voids play a key role in freestanding GaN substrate fabrication. Lin et al employed the GaN films grown on patterned sapphire substrate with large voids on the top region in the chemical lift-off process and found that the embedded voids can accelerate the wet etching process [17]. Bohyama et al acquired spontaneously separated freestanding GaN substrate by concentrating the compressive stress at the seeds because of the intentional formation of voids [18].…”
Section: Introductionmentioning
confidence: 99%